THE IMPACT OF ESG DISCLOSURE, COMPETITIVE ADVANTAGE, AND CASH HOLDING ON FINANCIAL PERFORMANCE AND FIRM VALUATION - Eny Maryanti; Ayu Faizatul Machmuda (Research Parks Publishers, 2026)
This study examines the influence of Environmental, Social, and Governance (ESG) Disclosure, Competitive Advantage, and Cash Holding on Financial Performance and Firm Value. Quantitative methods were used with secondary data from 50 companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The analysis was conducted using multiple linear regression. The results show that Cash Holding have a significant positive effect on Financial Performance and Firm Value. ESG Disclosure has no significant effect on Financial Performance or Firm Value, indicating that ESG practices are not yet a primary consideration for investors. Competitive advantage has a significant positive effect on financial performance, but not on firm value, indicating that competitive advantage has a greater impact on a company's internal operational efficiency than on market perceptions of firm value. This finding confirms that sustainability initiatives have not yet had a direct financial impact, while a strong competitive position has a significant impact on firm performance. This study provides important insights for managers and investors in decision making.